Electronic and Lattice Dynamical Properties of the Iron-Based Superconductors LiFeAs and NaFeAs - R. A. Jishi; H. M. Alyahyaei (Advances in Condensed Matter Physics)
The electronic structure and lattice vibrational frequencies of the newly discovered superconductors, LiFeAs and NaFeAs, are calculated within density functional theory. We show that, in the vicinity of the Fermi energy, the density of states is dominated by contributions from Fe 3d states. We also calculate the electron-phonon coupling strength and show that it is too weak to account for the observed values of the superconducting transition temperatures. This seems to indicate that the iron-based superconductors are not of the conventional type.